Experiences of acute pain in children who present to a healthcare facility for treatment: a systematic review of qualitative evidence. - Pope, Nicole; Tallon, Mary; McConigley, Ruth; Leslie, Gavin; Wilson, Sunni (Joanna Briggs Institute, 2017)
BACKGROUND: Pain is a universal and complex phenomenon that is personal, subjective and specific. Despite growing knowledge in pediatric pain, management of children's pain remains sub-optimal and is linked to negative behavioral and physiological consequences later in life. As there is no synthesis of these studies, it was timely to undertake a systematic review.